2010
DOI: 10.1017/s0950268810001007
|View full text |Cite
|
Sign up to set email alerts
|

Five hepatitis B outbreaks in care homes in the UK associated with deficiencies in infection control practice in blood glucose monitoring

Abstract: Healthcare-associated hepatitis B virus (HBV) outbreaks have been reported in the USA and from several countries in Europe. Patient-to-patient transmission of HBV in these settings has been linked to several different types of exposure but one of the most common exposures implicated is the use of 'finger-stick' lancet devices for blood glucose testing. This article is an account of the investigations into a series of HBV outbreaks linked to the use of lancing devices in community healthcare settings in the UK.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…14 Hepatitis B virus infection outbreaks due to infection control breaches and equipment misuse during the delivery of AMBG have been identified with increasing frequency over the past few decades. [3][4][5][6][7][8][9][10] Increasing prevalence and diagnosis of diabetes among the aging U.S. population 21,22 along with increasing reliance on AMBG services indicate that there will be a growing at-risk population. There is a need for renewed and improved prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Hepatitis B virus infection outbreaks due to infection control breaches and equipment misuse during the delivery of AMBG have been identified with increasing frequency over the past few decades. [3][4][5][6][7][8][9][10] Increasing prevalence and diagnosis of diabetes among the aging U.S. population 21,22 along with increasing reliance on AMBG services indicate that there will be a growing at-risk population. There is a need for renewed and improved prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…8 Investigators from the United Kingdom similarly concluded that confusion regarding the correct use of BG monitoring equipment was a contributing factor to HBV transmission. 6 They reported that models intended for self-use (i.e., SMBG) and professional use (i.e., AMBG) were very difficult to distinguish from one another and that the manufacturer's information that accompanies devices was often unclear. Ultimately, the accountability for providing safe care rests with the facilities and personnel who are providing AMBG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures can lead to situations where syringes, needles and blood glucose monitoring devices are shared (1)(2)(3) . The literature describes various outbreaks of hepatitis B in DM patients (3)(4)(5) . In 2011, the Advisory Committee on Immunization Practices of the Centers for Disease Control and Prevention (CDC) in the United States, recommended, based on evidence, hepatitis B vaccination for DM patients from ages 19 to 59, once a diagnosis is made, and for those aged 60 and older, after assessment of the risk and likelihood of an adequate immune response to vaccination (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence show that hepatitis B infection occurs more frequently among individuals with type 2 diabetes than the general population [1][2][3]. The odds for developing acute hepatitis B for individuals with diabetes is said to be as much as twice that for non-diabetics.…”
Section: Introductionmentioning
confidence: 99%